DEVELOPMENT OF SOFT COMPETENCES OF MANAGEMENT STAFF IN THE HIGHER EDUCATION SYSTEM: STRUCTURE, COMPONENTS AND THEIR FUNCTIONAL SIGNIFICANCE (Universal International Scientific Journal, 2026)
In this article, the problem of developing soft competencies of managerial personnel isanalyzed based on modern pedagogical and management theories. The essence of soft competencies,the structure of their development, the main components, and their functional significance inmanagement activities are scientifically and theoretically substantiated. The research results are of greatimportance in improving the system of training and advanced training of managerial personnel
Keywords: soft-competence; management; management activities